Sociologia do Babaçu: condições econômicas e sociais de reprodução camponesa no estado do Maranhão - Viana, Regina Stela de Melo (1985)
The babaçu-nut, which is the main exportation product of Maranhão, gibes rise today to a technical and political interest, from a national and international viewpoint. For as much its almond is traditionally a raw material for oil production, as, now, the coal obtained from its ligneous rod is wanted by siderurgical factories, because it has strong energetic power, and, besides, has no sulphur in this composition. In the babassu grove region, which occupies ever 100.000 km2 in Maranhão, there is an important amount of human population withdrawing their earnings for survivial from the babassu nut‟s exploitation, either drawing out the almonds, or producing coal. The nut‟s breaking is typically made women, and children. There is even a prejudge about men‟s work in the babassu. Earnings obtained in this activity are, sufficient, which are face the costs with the activities for subsistence, which are exercised mainly by men. The substitution of a handly breaking by a mechanic one, started in the midst 1970‟s, has not yet modified the general aspect of a primitive technology. There is too a lacking in the structure of commercialization, giving easily way to the foreigner profiteer. This confirms the Oliveira‟s thesis according to which there is a “primitive accumulation” characterized by expropriation of the surplus in the rural economies. This results from a field survey undertaken in the big counties of Chapadinha and Varzea Grande with a representative sample. We consider, in conclusion, some structural, institutional, and political aspects to be order to reach a stage of modernization and industrialization, and to preserve the babassu grove.